Diagnostic, Therapeutic, and Prognostic Value of the Thrombospondin Family in Gastric Cancer - Lu, Yi; Kong, Xianhe; Zhong, Weijie; Hu, Minhui; Li, Chujun (Frontiers in Molecular Biosciences, 2021)
Background: Gastric cancer (GC) is the fifth leading cancer in the world, the dysregulated expressions of the thrombospondin (THBS) family were reported to associate with GC, but their relations with tumor stage, prognosis, and correlations with tumor immunity have not been systematically reported. Methods: We used versatile public databases such as Oncomine, GEPIA, UALCAN, Kaplan-Meier Plotter, LinkedOmics, STRING, cBioportal, TIMER and TISIDB to analyze the expression and mutations of different THBSs in GC, along with their functional networks, survival analysis and tumor-immune interactions. Results: The mRNA levels of THBS2, THBS4 and COMP were significantly higher in the tumor tissues; the expression levels of THBS1, THBS2, and THBS4 were higher in stage 2-4 than that of stage 1; patients with high expression of THBS1, THBS2, THBS4 and COMP had poor OS; the genes correlated with THBSs were enriched in focal adhesion, glycosaminoglycan biosynthesis, ECM-receptor interaction, and hedgehog signaling pathway; THBS1 and THBS4 expression had significant correlations with tumor purity, and that all the THBSs expression correlated with macrophage and dendritic cells infiltration. Conclusion: THBS2, THBS4 and COMP were potentially diagnostic markers for GC; THBS1, THBS2, THBS4 and COMP were potentially prognostic markers for GC; investigating the relations of THBSs and tumor immunology might help in immunotherapy of GC, while more studies are needed to confirm these results.